2011
DOI: 10.1073/pnas.1115973108
|View full text |Cite
|
Sign up to set email alerts
|

Dextran hydrogel scaffolds enhance angiogenic responses and promote complete skin regeneration during burn wound healing

Abstract: Neovascularization is a critical determinant of wound-healing outcomes for deep burn injuries. We hypothesize that dextran-based hydrogels can serve as instructive scaffolds to promote neovascularization and skin regeneration in third-degree burn wounds. Dextran hydrogels are soft and pliable, offering opportunities to improve the management of burn wound treatment. We first developed a procedure to treat burn wounds on mice with dextran hydrogels. In this procedure, we followed clinical practice of wound exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
307
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 467 publications
(329 citation statements)
references
References 41 publications
8
307
2
2
Order By: Relevance
“…The burn injury was performed as previously reported. [36] Briefly, mice were first anesthetized, then the dorsum was shaved and cleaned with alcohol. A 1.2 cm diameter third degree burn was then generated.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The burn injury was performed as previously reported. [36] Briefly, mice were first anesthetized, then the dorsum was shaved and cleaned with alcohol. A 1.2 cm diameter third degree burn was then generated.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work indicated that amine group could also increase the biocompatibility. [40] It is worthy to note that our prior study demonstrated that a dextran-based (Dex-AE/PEGDA,80/20) hydrogel could promote full dermal regeneration with skin appendages on a murine third degree burn injury, [36] but the skin regeneration was incomplete during preclinical studies. [37] In this formula, polyethylene glycol (PEG) was not biodegradable and could also have potentially caused immobilization due to its hydrophilicity, which repels cell infiltration.…”
Section: Bioabsorbable Dextran-derived Macromersmentioning
confidence: 99%
See 3 more Smart Citations